SROI Community Based Cost-Benefit Analysis, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
What really matters to farmers? Researchers conducted interviews and workshops in Kochiel, Kenya to determine the costs and benefits of priority adaptation and mitigation strategies. This participatory Social Return of Investment (SROI) research is part of our work on Adaptation to Progressive Climate Change and Pro-poor Climate Change Mitigation.